2021
DOI: 10.3390/foods10102358
|View full text |Cite
|
Sign up to set email alerts
|

Food Loss and Waste Actions: Experiences of the Costa Rican Food Loss and Waste Reduction Network

Abstract: Food Loss and Waste (FLW) reduction and prevention can be crucial entry points to achieve sustainable food systems. However, the complexity of this problem poses the need for multistakeholder and multidimensional approaches. The Costa Rican FLW Reduction Network has been working since 2014 as a collaborative platform that brings together different sectors and disciplines to promote a change through communication and awareness, alliances, and research and innovation. The purpose of our study was to share the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Therefore, strategies on reduction of plate waste in school feeding should not only consider children's preferences and nutritional quality, but the actual impacts from nutritional, economic and environmental standpoints should also be addressed in such effort ( 49 ) . The Costa Rican food loss and waste reduction network indicated that collaborative actions among institutions and sectors are vital in promoting food loss and waste reduction ( 50 ) . It should be noted that the management of plate waste and food waste did not exist in both schools of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, strategies on reduction of plate waste in school feeding should not only consider children's preferences and nutritional quality, but the actual impacts from nutritional, economic and environmental standpoints should also be addressed in such effort ( 49 ) . The Costa Rican food loss and waste reduction network indicated that collaborative actions among institutions and sectors are vital in promoting food loss and waste reduction ( 50 ) . It should be noted that the management of plate waste and food waste did not exist in both schools of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Food supply chains require systemic and integrated approaches to address the complex dynamics among stakeholders, subsectors, and life cycle stages of products [ 13 ]. For this purpose, life cycle assessment (LCA) is recognized as a powerful tool for performing the potential environmental assessment of impacts and resource consumption throughout a product’s life cycle [ 14 ].…”
Section: Introductionmentioning
confidence: 99%